Changes in the global burden of foreign body aspiration among under-5 children from 1990 to 2019 - Wu, Yuying; Zhang, Xin; Lin, Zaigang; Ding, Chenyu; Wu, Yuxuan; Chen, Yue; Wang, Desheng; Yi, Xuehan; Chen, Fa (Frontiers in Pediatrics, 2023)
Background To evaluate the changes in the global burden of foreign body aspiration (FBA) among children under 5 years old at regional, age, sex, and socio-demographic index (SDI) levels between 1990 and 2019. Methods Data on FBA was derived from the Global Burden of Disease (GBD) Study 2019 database on pulmonary aspiration and foreign body in airway. The means and 95% uncertainty intervals (UIs) were calculated for incidence, and disability-adjusted life-years (DALYs). The temporal trends were represented by estimated annual percentage change (EAPC) using Joinpoint regression.Globally, FBA caused 109.6 (95% UI: 69.5, 175.7) per 100,000 incidence and 317.9 (95% UI: 270.7, 372.4) per 100,000 DALYs under 5 years old in 2019. Many European countries (such as Italy, Netherlands, Iceland, etc.) showed a high incidence rate, but did not cause a large disease burden (DALYs all less than 200 per 100,000).Compared to 1990, although a decrease in both incidence and DALYs occurred in 2019, the Joinpoint regression showed an increasing trend in incidence rate from 2014 to 2019 [APC: both (2.10), female (2.25), male (1.98), P<0.05)], especially China, Netherlands, and Malta. Despite the lower incidence rate in early neonatal group and middle SDI areas, they instead resulted in higher DALYs than other age groups and areas.Although declines occurred in incidence and DALYs of FBA among children under 5 years of age from 1990 to 2014, an upward trend began to emerge from 2014 to 2019. The incidence and DALY rates were correlated with age and SDI.Increased efforts are needed to improve the necessary monitoring and reporting systems, hazard assessment, and public education activities.